155k views
2 votes
What is the justification for each step in the

solution of the equation?

7 − 10 = 2(−3 + 8)
7 − 10 = 2(−3 + 8)
7 − 10 = −6 + 16
7 = −6 + 26
13 = 26
= 2

1 Answer

1 vote
to get from 7-10=2(-3+8) to 7-10=-6+16, you have to use the distributive property because of the parenthesis. the next step would be adding 10 to both sides in order to even the equation (adding because it cancels out the negative and makes 0), and the last step you have is adding 6 to both sides of the equation to balance it. in order to get 2, you have to divide 26 by 13 (26/13). hope this helps!
User Marleny
by
5.4k points